A one-dimensional model for predicting the temperature distribution in stratified water thermal storage tanks - Santos, Arturo Martin B. (1988, 1988)
A one-dimensional model for predicting the temperature distribution in an underground stratified water thermal storage tank was developed using fundamental thermodynamic principles. It was determined that a one-dimensional model, with an empirical adjustment to account for diffusion, is sufficient in predicting the temperature distribution in a thermally stratified storage tank. if the walls are considerably insulative. It was also ascertained that if the walls of the tank in contact with the water in storage were made of materials that conducted a significant amount of heat, then an additional parameter must be incorporated to account for this.
Thesis (M.S. Energy Engineering)--University of the Philippines Diliman.
Typescript.
Keywords: Heat storage; Cooling; Storage tanks; Water-storage.